Island Home - Stanley, B. (LiNQ (Literature in North Queensland), 2016)
My father was among other things a bush carpenter and with the help of a Norwegian neighbour, who had been a boat builder in his native country, he built our house on The Island. The Island has a different name now, and it does not look as it used to when I was a child. I was born in that modest house towards the end of the Depression and I came in feet first. It was accepted as the natural things for mothers to give birth in their own homes with a trusted midwife in attendance, and large families were the norm. I was the second youngest of nine children. I had five sisters and three brothers.